Critical loss of the balance between Th17 and T regulatory cell populations in pathogenic SIV infection. - David Favre; Sharon Lederer; Bittoo Kanwar; Zhong-Min Ma; Sean Proll; Zeljka Kasakow; Jeff Mold; Louise Swainson; Jason D Barbour; Carole R Baskin; Robert Palermo; Ivona Pandrea; et al. (PLoS Pathogens)
Chronic immune activation and progression to AIDS are observed after SIV infection in macaques but not in natural host primate species. To better understand this dichotomy, we compared acute pathogenic SIV infection in pigtailed macaques (PTs) to non-pathogenic infection in African green monkeys (AGMs). SIVagm-infected PTs, but not SIVagm-infected AGMs, rapidly developed systemic immune activation, marked and selective depletion of IL-17-secreting (Th17) cells, and loss of the balance between Th17 and T regulatory (Treg) cells in blood, lymphoid organs, and mucosal tissue. The loss of Th17 cells was found to be predictive of systemic and sustained T cell activation. Collectively, these data indicate that loss of the Th17 to Treg balance is related to SIV disease progression.